Обліково-аналітичне забезпечення управління доходами підприємства в ринкових умовах - Баленко, Валерія Денисівна; Balenko, Valeriya Denysivna (Ірпінь, 2024)
У кваліфікаційній роботі розкрито питання методики обліково-аналітичного забезпечення управління доходами підприємства, проведення аналізу основних доходів досліджуваного підприємства з метою надання рекомендацій щодо удосконалення системи управління доходами ПАТ «ПРЕСТИЖ БУД СТИЛЬ». Аналіз основних доходів дослідженого підприємства, що допоможе прийняти виважені управлінські рішення щодо оптимізації доходів на основі проведеного аналізу. За результатами дослідження сформульовані практичні рекомендації для покращення процесів управління доходами підприємства.

In the qualification work, the question of the method of accounting and analytical support for the management of the enterprise's income, the analysis of the main income of the investigated enterprise with the aim of providing recommendations for improving the income management system of PJSC "PRESTIZH BUILD STYLE" is disclosed. Analysis of the main revenues of the investigated enterprise, which will help to make balanced management decisions regarding the optimization of revenues based on the conducted analysis. Based on the results of the study, practical recommendations were formulated to improve the company's revenue management processes.
Accounting and analytical support for enterprise income management in market conditions
Keywords: будівельне підприємство; доходи; фінансова звітність; обліково-аналітичне забезпечення управління доходами; облік і аналіз доходів підприємства; construction enterprise; revenues; financial reporting; accounting and analytical support for revenue management; accounting and analysis of enterprise revenues